The Neotropical species Askalaphium depressum (Bates): Larval description, first diagnosis and illustrations of immature Ctenodactylini, with natural history notes on the genus and tribe (Coleoptera: Carabidae) - Erwin, Terry L.; Medina, Raul F. (Zootaxa, 2003)
Adults and larvae of Askalaphium depressum (Bates) live in association with hispine chrysomelid beetles of the genus Cephaloleia Chevrolat, in the appressed leaf axils of the riverside reed, Gynerium sagittatum (Aubl.) P. Beauv. This reed is locally known in Amazonian Perú as Caña Brava. Both adult and larval A. depressum eat larvae of Cephaloleia species and larvae of an unidentified dipteran, and perhaps other insects living in the confines of the leaf sheaths of that plant species. The geographic range of Caña Brava reed extends from subtropical South America northward to México (and Florida), but A. depressum has been found thus far at only three Amazonian localities, probably indicating its cryptic microhabitat and lack of collecting, therein. Likely, the range of this commensal carabid species is more extensive and may approach the range of its host plant and hispine food. Structural features of second and third instar larvae of A. depressum are described for the first time. Larval character states that are shared with a related ctenodactyline, Leptotrachelus dorsalis (Fabricius), provide a basis for characterization of the tribe Ctenodactylini.